Democracia cosmopolita : una solución probable a problemas de justicia global en términos de pobreza = Cosmopolitan democracy : a likely solution to problems of global justice in terms of poverty global justice in terms of poverty (2018)
This paper proposes a normative and empirical approach to the phenomenon of poverty in order to argue how the establishment of a democratic institutional design on an international scale would increase the probability of having fair distributive outcomes in terms of global justice. In this sense, firstly, the relationship between the notion of global justice and the approach to the phenomenon of poverty in moral terms is discussed; secondly, the relationship between democratic institutions and the distribution of resources is elucidated; and finally, a democratic institutional design at the international level or a "cosmopolitan democracy" is proposed as an institutional design that would guarantee fair economic distributions at the global level